(untitled) (Semiárida, 2020)
The objective of this study was to measure the effect of soya bean supplementation on some ruminal parameters. A diet composed of rye grass hay was given to Holstein-Freisian dry cows fitted with permanent rumen fistulae, with (CS) or without (SS) supplementation of 1 Kg soya bean meal per cow day. Samples of rumen content were withdrawn at 0, 2,4, 6,8; and 10 hours after supplementation, simultaneously for both treatments. The samples were processed for: ammonia, ATP and volatile fatty acids (AGV) concentration, AGV composition and rumen bacterial counts. Significant differences between treatments were found for ammonia concentration (CS: 86.4 mg/l; ss. 53.7 mg/I; P<0.01), number of bacteria (CS: 1.11 x 109; SS: 0.68x 109; P<0.01) and propionic acid concentration (CS: 16.8 mmol/I; SS: 15.4 mmol/I; P<0.01) and also between sampling times for ATI’ concentration, in both treatments, when zero hour (sample taken immediately before supplementation) was compared with 2, 4 and 6 hours (P<0.01): zero hour: 9.7 g ATP/g; two hours: 20.6 g/g; four hours: 19.7 g/g; six hours: 25.7 g/g. The number of rumen microbes was 62% higher in CS when compared to SS, indicating the effect of soya bean meal upon rumen population growth.